Kedudukan Alat Bukti Elektronik dalam Pembuktian Tindak Pidana - Hasnawati, Hasnawati; Safrin, Mohammad (Fakultas Syariah INSURI Ponorogo, 2023)
The legal implications caused by social change, especially technological developments (electronic devices) lie in the need for evidence by presenting electronic evidence in court. In Indonesian criminal law, the use of electronic evidence has actually been regulated. This study aims to determine and analyze the status of electronic evidence, especially in criminal trials after the enactment of the ITE Law and to find out the role of electronic evidence in Indonesian criminal law. Then it is reviewed and analyzed the characteristics and analysis of the electronic evidence so that it can be used as a reference for the judge's opinion in court. This search is a library search or literature search. The material is taken from various literature related to research. This journal writing method uses normative legal methods using statutory approaches and conceptual approaches. The results of the study show that the Criminal Procedure Code is still general in nature and does not recognize evidence in electronic form that can be used as a source of interest as evidence in court cases, electronic evidence itself is a form of expansion/development of evidence guidance so that in the Criminal Procedure Code the status is electronic evidence evidence.. Based on a survey on the status of electronic evidence in Indonesian criminal law, the status of electronic evidence according to ITE (Electronic Information and Transaction Law) is considered valid as long as the authenticity of the evidence can be proven and recognized by professionals. and submitted in accordance with applicable regulations.